2019
DOI: 10.1177/2332858419879446
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Mathematics Intervention Can Significantly Improve Student Learning Trajectories Through Elementary School

Abstract: Perhaps more than at any other time in history, the development of mathematical skill is critical for the long-term success of students. Unfortunately, on average, U.S. students lag behind their peers in other developed countries on mathematics outcomes, and within the United States, an entrenched mathematics achievement gap exists between students from more highly resourced and socially dominant groups, and minority students. To begin to remedy this situation, educational researchers have created instructiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 81 publications
0
13
0
3
Order By: Relevance
“…By the time children enter preschool there is tremendous variability in their math and science knowledge (e.g., Bullock, Sodian, & Koerber, 2009;McWayne, Cheung, Wright & Hahs-Vaughn, 2012;von Hippel, Workman & Downey, 2018) that influences their future rates of learning (Dumas, McNeish, Sarama & Clements, 2019). Both the frequency and quality of parental involvement in math and science activities explains some of this variability (e.g., Levine, Suriyakham, Rowe, Huttenlocher & Gunderson, 2010;Ramani, Rowe, Eason & Leech, 2015;Skwarchuk, 2009).…”
Section: Parental Involvement In Informal Learningmentioning
confidence: 99%
“…By the time children enter preschool there is tremendous variability in their math and science knowledge (e.g., Bullock, Sodian, & Koerber, 2009;McWayne, Cheung, Wright & Hahs-Vaughn, 2012;von Hippel, Workman & Downey, 2018) that influences their future rates of learning (Dumas, McNeish, Sarama & Clements, 2019). Both the frequency and quality of parental involvement in math and science activities explains some of this variability (e.g., Levine, Suriyakham, Rowe, Huttenlocher & Gunderson, 2010;Ramani, Rowe, Eason & Leech, 2015;Skwarchuk, 2009).…”
Section: Parental Involvement In Informal Learningmentioning
confidence: 99%
“…In the absence of intervention effects that persist throughout elementary school, there is debate about the policy ramifications of implementing interventions on a large scale (Bailey et al, 2018). Dumas et al (2019) applied nonlinear dynamic measurement growth models to data from a clustered randomized trial in children followed from preschool to Grade 5 and similarly found that the difference between the intervention and control groups diminishes over time. To probe aspects of timing, they applied a Michaelis-Menten model which estimated the time at which the outcome had developed to the midpoint between the intercept and asymptote.…”
Section: Model and Resultsmentioning
confidence: 99%
“…Twelve studies included LP-based assessments designed for summative purposes; research is required in this area as such tasks might more accurately measure learning growth promoted in an LP approach. Another limitation was that studies frequently relied on just two measurements of learning; Dumas et al (2019) argued that, as student learning is not linear, more complex models (e.g., dynamic measurement modeling) based on data collected across multiple time points are needed to understand learner trajectories and identify if learning growth is consistent over time.…”
Section: Discussionmentioning
confidence: 99%